Effect of nitrogen point placement on energetic and soil enzymatic activities on long-term conservation agriculture based maize (Zea mays) - wheat (Triticum aestivum) system of western Indo-Gangetic plains - NAYAK, H S; PARIHAR, C M; JAT, S L; LATA, LATA; MANDAL, B N; SINGH, V K; GARNAIK, S; MUDULI, L; SAHU, S (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was done in the long term conservation agriculture (CA)-based plots at ICAR-Indian Agricultural Research Institute (IARI) during 2018–19 with the treatments of nitrogen (N) point/line placement to compute the energy budgeting and soil enzymatic activity. There were four land management practices in main plots and in sub plots there were three nitrogen placement methods. Results of present study showed that the energy use efficiency was higher in the CA-based PB plots by 7.14% and 9.4% than CT plots in maize and wheat respectively. The energy output from the CA-based maize (Zea mays L.) and wheat (Triticum aestivum L.) plots was significantly higher by 9.1–11.2% and 8.8–14.4% than CT plots. However, N point placement treatments i.e. NPM3 and NPM2 had 14.8% and 8.8% higher energy output than NPM1 plots in maize respectively. Similarly in wheat, NPM2 and NPM3 plots had 4.2% and 7.0% higher energy output than NPM1. The CA-based plots recorded an increase in soil microbial biomass carbon (SMBC) by 8.7–15.6% in maize and 10.1–17.2% in wheat. The SMBC content remained statistically similar across N placement methods at flowering of maize and wheat crops. In maize and wheat, at the surface soil layer urease activity was found higher than CT by 11.7–20.2% and 13.2–22.4% in the CA-based plots. However, the urease activity was not affected by subsurface point or line placement of nitrogen at both the soil layers in both the crops. Therefore, the findings of present study suggest that the adoption of CA-based practices with point/line placement of split applied N in maize-wheat system of western Indo-Gangetic plains is favourable for improving the energy use efficiency and soil enzymatic activity.